A Review on Multilevel Approaches for Security in Cloud by Using ABE (International Journal of Innovative Research in Computer Science & Technology, 2019)
Public Key Encryption acts as the basic  technique for ABE where it provides one to many  encryptions, here, the private key of users & the cipher text both rely on attributes such that, when the set of the  attributes of users key matches set of attributes of  cipher-text with its corresponding access policy, only  then decryption is possible. Thus, an opponent could  grant access to the sensitive information that holds  multiple keys, if it has at least one individual key for  accession. Medical organizations find it challenging to  adopt cloud-based electronic medical records services,  due to the risk of data breaches and the resulting  compromise of patient data. Hence there is a need of  developing a proper authorization delegation mechanism  for safe, secure and easy cloud-based EHR  management.In this research work a centralized,  attribute based authorization mechanism is developed  that uses Attribute Based Encryption (ABE) and allows  for delegated secure access of patient records.
Keywords: Cloud computing; Data sharing; Data confidentiality; Security; ABE; Access controls